Geopolitical and Economic Aspects of Nuclear Energy - S. Z. Zhiznin; V. M. Timokhov (Vestnik MGIMO-Universiteta)
Nuclear power in its present form was created during the Cold War and is its heritage. The main objective of nuclear energy at that time, along with energy, was the creation and accumulation of nuclear materials. To this aim a existing nuclear power plants based on uranium-plutonium cycle. Everything else - the processing of radioactive waste and spent nuclear fuel, storage, recycling themselves nuclear power plant after its end of life, the risks of proliferation of nuclear materials and other environmental issues - minor. It was also believed that the nuclear power plant - the most reliable and safe plant. During the last twenty years all over the world the number of new orders for nuclear aggregates has decreased. That happens for a number of reasons, including public resistance, that the construction of new NPP and the excess of energy utilities in many markets, which is mainly connected with high market competition in energy markets and low economic indicators of the current nuclear utilities. The technology that consists of low capital costs, a possibility for quick construction and guarantied exploitation quality is on the winners side, but currently this technology is absent. However, despite abovementioned downsides, as the experience of state corporation "Rosatom"has shown, many developing countries of the South-east Asia, The middle East, African regions express high interest in the development of nuclear energy in their countries. The decision whether to develop nuclear energy or to continue to develop is, in the end, up to the choice of the tasks that a country faces. The article describes these "minor" issues, as well as geopolitical and economic problems of the further development of nuclear energy.